PROPHETIC VALUES-BASED SUPERVISION FOR PHYSICAL EDUCATION, SPORTS, AND HEALTH TEACHERS IN ELEMENTARY SCHOOLS IN TALUN DISTRICT, PEKALONGAN REGENCY - Lukman, Aslori Lukman; sulaiman (Universitas Negeri Semarang, 2025)
https://docs.google.com/document/d/18cawy1C0vSLHh7vAymjUf3b-oCxuNIUN/edit?usp=sharing&ouid=116139126395566775800&rtpof=true&sd=true